2012
DOI: 10.1155/2012/476763
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Incidentalomas Discovered by Whole Body FDG PETCT

Abstract: Objectives. To determine the prevalence of incidentalomas in a patient population with no known thyroid malignancy who underwent whole body FDG-PET/CT for staging or restaging of neoplasia. The additional aim of the study was to evaluate the feasibility of using PETCT as a screening tool for malignant thyroid incidentalomas. Methods. Retrospective review of medical records of all the thyroid exams done at our institution between January 1, 2000 and August 20, 2008. We made a criterion of PET/CT as the primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…The significance of incidental focal thyroid uptake on 18 F-FDG PET study was first described in 2001 [10]. Many research studies are currently available on this topic, with different results on focal uptake of tracer on 18 F-FDG PET [3,4,5,6,8,9,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38]; however, a large UK series has yet to be reported. We report one of the largest studies on the evaluation of incidental focal 18 F-FDG uptake in the thyroid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of incidental focal thyroid uptake on 18 F-FDG PET study was first described in 2001 [10]. Many research studies are currently available on this topic, with different results on focal uptake of tracer on 18 F-FDG PET [3,4,5,6,8,9,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38]; however, a large UK series has yet to be reported. We report one of the largest studies on the evaluation of incidental focal 18 F-FDG uptake in the thyroid.…”
Section: Discussionmentioning
confidence: 99%
“…Literature evidenceon the SUV max in benign and malignant lesions vary with several reports showing a statistically significant difference [9,13,19,21,22,23,34,41] whilst many others have shown no significant difference [8,14,15,27,30,32,33,35,36]. Previous studies have also reported cutoff SUV values ranging from 3.5 to 5 in differentiated benign to malignant thyroid lesions [24,34,41].…”
Section: Discussionmentioning
confidence: 99%
“…It is also utilized for cancer screening. 4 Diffuse type generally suggests a benign lesion since most cases are autoimmune thyroiditis, 5,6 with rare exceptions. 2 With the ever increasing use of FDG-PET in oncology, the reported incidence of PET-avid incidentalomas ranges between 0.2% and 8.9%.…”
mentioning
confidence: 99%
“…A diffuse type means increased FDG uptake in the whole thyroid gland, whereas with the focal type the area of increased uptake is limited to less than one lobe. 4 Diffuse type generally suggests a benign lesion since most cases are autoimmune thyroiditis, 5,6 with rare exceptions. However, focal FDG uptake carries certain risk of thyroid malignancy.…”
mentioning
confidence: 99%
See 1 more Smart Citation